Developing perennial upland rice. II: Field performance of S1 families from an intermated Oryza sativa/O. longistaminata population - Sacks, Erik J.; Roxas, Jose P.; Cruz, Maria Teresa Sta. (Wiley, 2003)
In Southeast Asia, upland rice (Oryza sativa L.) is an annual crop that is typically cultivated on hilly sites, contributing to the erosion of soil and the degradation of watersheds. We wish to develop a perennial upland rice that would help conserve natural resources via a permanent ground cover, while providing subsistence farmers with a valued food. Oryza longistaminata A. Chev. et Roehr. is a highly perennial, rhizomatous relative of O. sativa that may be a useful source of genes for developing perennial upland rice. This study was conducted to evaluate the potential of an O. sativa/O. longistaminata intermated population for developing perennial upland rice. As a baseline for comparison, none of the cultivar controls survived 1 yr. Among 94 S1 families, 1‐yr survival ranged from 0 to 63.6% but only six families had more than 30% survival. On the basis of observations at the soil surface, less than 1% of the progeny plants produced rhizomes. However, three families produced approximately 25% rhizomatous individuals, suggesting the presence of a single locus with large effect. Interspecific crossing barriers led to low S1 yields, with many plants being completely sterile. The low fertility and limited perenniality observed may make further breeding progress with this population difficult.